A regenerable screen-printed voltammetric Hg(II) ion sensor based on tris- thiourea organic chelating ligand grafted graphene nanomaterial - Suhaila, Sapari; Nurul Hidayah, Abdul Razak; Siti Aishah, Hasbullah; Heng, Lee Yook; Chong, Kwok Feng; Tan, Ling Ling (Elsevier, 2020)
An electrochemical Hg(II) ion sensor has been developed by using a miniaturized carbon paste screen-printed electrode (CSPE) modified with reduced graphene oxide (rGO) sheets and tris-thiourea (TTU) chelating ligand compound, i.e. N,N′,N″-((nitrilotris(ethane-2,1diyl))tris(azanediyl))tris(carbonothioyl))tribenz amide. In view of the strong cation-exchange characteristic and adsorption of aromatic TTU tridentate ligand on the graphene nanomaterial surface by non-covalent π–π stacking interaction, the differential pulse voltammetry (DPV) peak current response of the voltammetric sensor was linearly dependent on a broad Hg(II) ion concentration detection range from 0.1–00.0 mg L−1 with a limit of detection (LOD) estimated at 0.02 mg L−1 after accumulation for 10 min. The chemically modified miniaturized SPE showed high stability throughout the course of the sensor lifetime study for the detection of inorganic Hg(II) ion with a relative standard deviation (RSD) of the sensor response obtained at 1.2%. The electrochemical sensor is reusable up to three consecutive Hg(II) ion assays by using 0.05 M acetate buffer (pH 8) as the sensor regeneration solution with a reversibility RSD value of 3.9%. The voltammetric sensor based on TTU derivative element and rGO nanosheets revealed satisfactory selectivity for Hg(II) ion over a large number of potential interfering ions, e.g. Ca(II), Co(II), Cu(II), Fe(II), Ni(II), Na(I) and Zn(II), and demonstrated reliable quantitative results as compared to the results obtained with inductively coupled plasma-mass spectrometer (ICP-MS) standard method for Hg (II) ion detection in river water samples.